1997
DOI: 10.1111/j.2042-3306.1997.tb03141.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high volume epidural morphine, ketamine and butorphanol on halothane minimum alveolar concentration in ponies

Abstract: Summary This study determined the effects of epidurally administered morphine, ketamine and butorphanol on halothane minimum alveolar concentration (MAC) in ponies. Seven ponies were anaesthetised with thiopentone and succinylcholine, intubated and anaesthesia maintained with halothane. Ventilation was controlled and blood pressure was maintained within normal limits. Following the determination of baseline halothane MAC for the pelvic and thoracic limbs the ponies were given morphine (0.1 mg/kg bwt), ketamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 24 publications
2
42
0
2
Order By: Relevance
“…Epidural administration of ketamine and morphine to horses provides analgesia and decreases inhalant anesthetic requirements (see Table 1) [110]. Preoperative administration of these agents may be particularly useful in critically ill patients to reduce the risk of intraoperative hypotension (inhalant-sparing effect) and to provide preemptive and postoperative analgesia [110][111][112].…”
Section: Intraoperative Adjuncts To Decrease Anesthetic Requirementsmentioning
confidence: 99%
“…Epidural administration of ketamine and morphine to horses provides analgesia and decreases inhalant anesthetic requirements (see Table 1) [110]. Preoperative administration of these agents may be particularly useful in critically ill patients to reduce the risk of intraoperative hypotension (inhalant-sparing effect) and to provide preemptive and postoperative analgesia [110][111][112].…”
Section: Intraoperative Adjuncts To Decrease Anesthetic Requirementsmentioning
confidence: 99%
“…Reduction of isoflurane MAC by epidural morphine has been observed in other studies. For example, epidural morphine reduced halothane MAC by at least 33% in dogs (Valverde et al 1989) and 14% in ponies (Doherty et al 1997). In humans, it is reported that epidural morphine reduces the halothane MAC by 28% (Schwieger et al 1992) and isoflurane MAC by 14% (Kashyap et al 2003).…”
mentioning
confidence: 99%
“…Furthermore, these opioids have been reported to decrease minimum alveolar concentration (MAC) of the volatile anaesthetic when given preoperatively in many species (Valverde et al 1989, Steffey et al 1994, Doherty et al 2002. For instance, epidural morphine has been reported to reduce MAC of halothane in dogs (Valverde et al 1989), ponies (Doherty et al 1997) and the requirement of isoflurane in pigs (Malavasi et al 2006). Treatment with IM buprenorphine has been reported to reduce the MAC of halothane in humans (Inagaki & Kuzukawa 1997).…”
mentioning
confidence: 99%
“…O uso epidural de fármacos antinociceptivos possibilita intervenções urogenitais em eqüinos em estação (SKARDA, 1991;SALMON et al, 1995;DOHERTY et al, 1997), sendo que os anestésicos locais são utilizados, mas geram bloqueio motor e simpático além do sensorial (DE ROSSI et al 2005). Na busca de mais seletividade por fibras sensoriais, surgem os agonistas α 2 (LE BLANC & CARON, 1990;LE BLANC & EBERHART, 1990;GRUBB et al, 1992).…”
Section: Introductionunclassified